MODFLOW-based groundwater level prediction and comprehensive determination of anti-floating water level for airports under construction - Kong, Xiaoyun; An, Haibo; Hao, Mingsheng; Zhang, Changlong; Yang, Congcong; Jia, Tao; Wang, Xi; Wang, Shanlin; Liu, Shiliang (Frontiers in Earth Science, 2025)
The fluctuation of the groundwater level at a construction site is crucial in determining the design of the anti-floating water level. The design of the anti-floating water level is mainly based on the water level measured during the survey period combined with the information acquired from surrounding engineering. However, this approach fails to predict the future variation of groundwater level, which can potentially endanger the safety during the construction process and building occupancy. Therefore, a comprehensive method for determining the anti-floating water level is proposed based on the research background of expanding the airport site in Jinan. In conjunction with the actual survey of the expanded airport, numerical simulation research is conducted to predict the anti-floating water level under groundwater changes at three different depths of 3, 8, and 16 m. The anti-floating water levels corresponding to the depths are 19.2–18.3 m, 19.1–18.3 m, and 18.9 m−18.1 m, respectively. The analysis of the changes in groundwater level and precipitation in the site reveals a linear relationship between groundwater level and precipitation during January 2018 to December 2022. In addition, a quantitative theoretical calculation method for anti-floating water levels is proposed. Finally, a comprehensive comparison is performed between the anti-floating water level based on groundwater level and rainfall data and the simulated anti-floating water level. The measured and simulated anti-floating water levels are essentially the same in the western part of the study area, while the anti-floating water level obtained from the numerical simulation is lower in the southeast and higher in the northeast region. On this basis, the highest value among the measured and simulated is taken, and the anti-floating water level of the site is divided. The anti-floating measurements are proposed.